Consumers' Perceptions, Attitudes and Willingness to Pay Towards Chemical Free Produce : The Case of Vegetable - Mohd Nawi, Nolila (2001)
This study was aimed to determine consumers' perceptions, attitudes and willingness to pay (WTP) towards chemical free vegetable (CFV) produce. A total of 2258 respondents were interviewed using a close-ended questionnaire. Collected data was analysed using descriptive analysis, factor analysis and contingent valuation method (CVM). The results indicated that only a small percentage of consumers had ever consumed CFV although they had heard about it. The results also suggested that lack of knowledge was the main reason for the consumers not consuming CFV. Nutritional value was the most important factor that influences consumers' preferences in purchasing CFV, followed by freshness, health, taste and desire. The factor analysis results identified six factors that influenced the purchasing of CFV among Malaysian consumers. The factors were awareness of chemical use, government involvement, health conscious, product availability, information awareness and product appearance. The CVM was used to estimate consumers' WTP for CFV. A logit and probit model was used to determine consumers' WTP a premium for CFV. The results indicate that household income and price levels were the most important and significant factors that influenced and determined the amount of premium that a consumer is willing to pay for CFV. Based on the study, it was found that at present CFV market is still a niche market, catering only a small segment of a whole vegetable market. Generally, Malaysians are still very reluctant to purchase CFV produce. Thus, to ensure a proper development of CFV market, there is a need to establish standards and certification programmes for CFV and to intensify Research and Development (R&D) to generate more cost effective production technologies for CFV.